Relationship between the neutrophil-to-lymphocyte ratio or platelet-to-lymphocyte ratio and deep venous thrombosis (DVT) following femoral neck fractures in the elderly - Niu, Shuai; Pei, Yueying; Hu, Xin; Ding, Dianzhu; Jiang, Guangwei (Frontiers in Surgery, 2022)
Purpose: This study aimed to investigate whether the neutrophil to lymphocyte ratio (NLR) or platelet to lymphocyte ratio (PLR) was associated with deep venous thrombosis (DVT) following Femoral Neck Fracture in the Elderly. Method: This was a retrospective cohort study, using data extracted from the hospitalization electronic medical record and the laboratory biomarker reports. Patients were included if they were aged above 60 years with definite diagnosis of femoral neck fracture caused by low-energy trauma. Duplex ultrasound (DUS) scanning was routinely performed to detect the potential DVTs. Two independent multivariate logistics regression models were constructed to identify the association of NLR or PLR with risk of DVT. Results: Totally, 708 patients with femoral neck fracture were included and 112 were found to have DVTs, indicating the incidence rate of 15.8%. There were significant differences across 5 subgroups for NLR or PLR, in term of age (p=0.020, 0.006), WBC (p=<0.001, 0.006), HGB (p<0.001, <0.001) and ALB (p<0.001, <0.001). BMI was tested to be significantly different across subgroups for NLR (p=0.030), and prevalence of cerebrovascular disease for PLR (p=0.014). The multivariate analyses demonstrated not NLR, but PLR in Q3 (range, 179-238) was associated with increased risk of DVT; and the risk for the latter was 1.86 (95%CI, 1.07 to 3.36). Conclusion: We concluded that PLR value of 179-238 was associated with 1.86-time increased risk of DVT after femoral neck fracture. This study paves a way towards further exploration of inflammatory/immune biomarkers with the risk of DVT in the elderly with trauma.